2005
DOI: 10.1093/toxsci/kfi246
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards Development of an Amphibian-Based Thyroid Screening Assay Using Xenopus laevis. Organismal and Thyroidal Responses to the Model Compounds 6-Propylthiouracil, Methimazole, and Thyroxine

Abstract: In response to the initial Endocrine Disruptor Screening and Testing Advisory Committee (EDSTAC) recommendations, research was conducted on the development of a Xenopus laevis based tail resorption assay for evaluating thyroid axis disruption. This research highlighted key limitations associated with relying on tail resorption as a measure of anti/thyroid activity. The most critical limitation being that tail tissues of tadpoles at metamorphic climax are insensitive to perturbation by thyroid axis agonists/ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 36 publications
(44 reference statements)
9
81
0
Order By: Relevance
“…By contrast, PTU treatment at pre-metamorphic stage (stages 26-27) blocks larval development but it seems to bear no significant effect on pro-metamorphic tadpoles (stages 29-30). This last result is consistent with recent observations in the African clawed frog in which it was demonstrated that late pro-metamorphic tadpoles are practically insensible to inhibitors of T 4 synthesis, such as thiourea or metilazolo (Degitz et al, 2005). However, either in pre-or in pro-metamorphosis, PTU injections lead to a significant increase (more than 2-fold) in the brain MC population.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, PTU treatment at pre-metamorphic stage (stages 26-27) blocks larval development but it seems to bear no significant effect on pro-metamorphic tadpoles (stages 29-30). This last result is consistent with recent observations in the African clawed frog in which it was demonstrated that late pro-metamorphic tadpoles are practically insensible to inhibitors of T 4 synthesis, such as thiourea or metilazolo (Degitz et al, 2005). However, either in pre-or in pro-metamorphosis, PTU injections lead to a significant increase (more than 2-fold) in the brain MC population.…”
Section: Discussionsupporting
confidence: 92%
“…Methimazole (1-methyl-2-imidazolethiol) is a known inhibitor of thyroperoxidase, the enzyme responsible for synthesizing thyroid hormones. Methimazole has previously been shown to significantly inhibit the rate of X. laevis development and to affect thyroid gland histology at concentrations !12.5 mg/L [18,19]. L-thyroxine (T4) is the major thyroid hormone synthesized by the thyroid gland in vertebrates.…”
Section: Test Chemicalsmentioning
confidence: 99%
“…In the literature, Xenopus laevis is the most-used model species for studying thyroid disrupting effects (Degitz et al, 2005;Heimeier et al, 2009). Given the obtainability of experimental animals, some native amphibian species, such as Rana catesbeiana and Rana pipiens (Helbing et al, 2006;Croteau et al, 2009), Rana temporaria (Arukwe and Jenssen, 2005;Gutleb et al, 2000) and Rana rugosa (Hanada et al, 2003;Oka et al, 2009), are used to assess effects of chemicals on the thyroid system.…”
Section: Introductionmentioning
confidence: 99%